T-cell agonists in cancer immunotherapy - Gennaro Ciliberto; Aung Naing; Joud Hajjar; Cara L Haymaker; Yeonjoo Choi; Yaoyao Shi (Journal for ImmunoTherapy of Cancer)
Cancer cells can evade immune surveillance in the body. However, immune checkpoint inhibitors can interrupt this evasion and enhance the antitumor activity of T cells. Other mechanisms for promoting antitumor T-cell function are the targeting of costimulatory molecules expressed on the surface of T cells, such as 4-1BB, OX40, inducible T-cell costimulator and glucocorticoid-induced tumor necrosis factor receptor. In addition, CD40 targets the modulation of the activation of antigen-presenting cells, which ultimately leads to T-cell activation. Agonists of these costimulatory molecules have demonstrated promising results in preclinical and early-phase trials and are now being tested in ongoing clinical trials. In addition, researchers are conducting trials of combinations of such immune modulators with checkpoint blockade, radiotherapy and cytotoxic chemotherapeutic drugs in patients with advanced tumors. This review gives a comprehensive picture of the current knowledge of T-cell agonists based on their use in recent and ongoing clinical trials.